2004
DOI: 10.1029/2003gb002154
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen deposition and increased carbon accumulation in ombrotrophic peatlands in eastern Canada

Abstract: [1] Recent and long-term accumulation rates of carbon (C), using 210 Pb-and 14 C-dating, were examined in 23 ombrotrophic peatlands in eastern Canada, where average 1990-1996 atmospheric wet nitrogen (N) deposition ranged from 0.3 to 0.8 g N m À2 yr À1 . The average recent rate of C accumulation (RERCA) over the past 150 years was 73 ± 17 (SD) g C m À2 yr À1 , ranging from 40 to 117 g C m À2 yr À1. The difference in RERCA between hummocks (78 g C m À2 yr À1 ) and hollows (65 g C m À2 yr À1 ) was significant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
121
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(138 citation statements)
references
References 68 publications
13
121
4
Order By: Relevance
“…A key characteristic of ombrotrophic bogs is that N, P and other elements (e.g., Ca, K, Mg) vital to their biogeochemical functioning (Bridgham et al, 1998;Bubier et al, 2007;Damman, 1986) and plant assemblage structure (Baker and Boatman, 1990;Fritz et al, 2012;Gotelli et al, 2008) are almost exclusively supplied via the atmosphere (Damman, 1990;Kellogg and Bridgham, 2003;Malmer, 1988). Such inputs of N and P are estimated to be low (Tipping et al, 2014;Turunen et al, 2004), suggesting that their availability should limit peat bog primary production (Schlesinger and Bernhardt, 2013), an effect that has been demonstrated experimentally (Aerts et al, 1992;Aerts et al, 2001;Olid et al, 2014). Although they are both supplied from the atmosphere, N and P differ in the mechanisms by which this supply takes place.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key characteristic of ombrotrophic bogs is that N, P and other elements (e.g., Ca, K, Mg) vital to their biogeochemical functioning (Bridgham et al, 1998;Bubier et al, 2007;Damman, 1986) and plant assemblage structure (Baker and Boatman, 1990;Fritz et al, 2012;Gotelli et al, 2008) are almost exclusively supplied via the atmosphere (Damman, 1990;Kellogg and Bridgham, 2003;Malmer, 1988). Such inputs of N and P are estimated to be low (Tipping et al, 2014;Turunen et al, 2004), suggesting that their availability should limit peat bog primary production (Schlesinger and Bernhardt, 2013), an effect that has been demonstrated experimentally (Aerts et al, 1992;Aerts et al, 2001;Olid et al, 2014). Although they are both supplied from the atmosphere, N and P differ in the mechanisms by which this supply takes place.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is conflicting evidence about the possible role of recent (20th Century) anthropogenically-driven atmospheric nutrient enrichment (Galloway et al, 2004;Vitousek et al, 1997). Malmer (1988) observed a latitudinal gradient of bog surface N concentrations that reflected the deposition rates across Sweden and Norway (Malmer, 1988), while Gorham and Janssens (2005) found no recent increase at sites across North America despite high N deposition (Turunen et al, 2004). Where observed, increases in N concentration with depth have been attributed primarily to preferential decay and loss of C during progressive decomposition of the plant-derived organic matter (Malmer and Holm, 1984;Craft and Richardson, 1993;Kuhry and Vitt, 1996;Malmer and Wallén, 2004;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of increased N availability is less straight-forward because a small increase in N can enhance Sphagnum production at locations where N is a limiting nutrient (Turunen et al 2004). However, when N concentrations exceed a critical threshold value, Sphagnum production and cover are reduced (Berendse et al 2001;Gerdol et al 2007;Gunnarsson and Rydin 2000;Lamers et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Neff et al (2002) reported that global atmospheric N deposition varies from 25 to 40 TgN y −1 and will be doubled in the next 25 years. The input of plant-available N promotes C sequestration of N-limited forest ecosystems by increasing net primary production, and delays, to a certain degree, the increase of atmospheric CO 2 concentration (Mäkipää et al 1999;Turunen et al 2004). However, other studies indicate that N saturation resulting from excessive N input will accelerate the plant mortality, and thus weaken potential C sequestration of forest ecosystems (Nadelhoffer et al 1999;Stevens et al 2004).…”
Section: Introductionmentioning
confidence: 99%